Strategy for the Training of Environmental Historians in the 21st Century - Morales-Jasso, Gerardo; Espinosa, Laura Yáñez; Badano, Ernesto Iván (Historia Ambiental Latinoamericana y Caribeña (HALAC) revista de la Solcha, 2024)
Environmental history has been practiced by professionals from various disciplines who are traditionally trained in history, anthropology, geography, and other social sciences or humanities. There are even environmental historians who have been trained as natural scientists. This has generated a paradigmatic dispersion: the issues addressed by environmental history generate a problem of cetacean dimensions. At the same time, the environmental sciences have dealt with similar problems, which is why, for the 21st century, the strategy proposed is that historians who become environmental historians study postgraduate studies in environmental sciences. Some advantages that this would bring to environmental history are discussed, and it addresses the example of the Programa Multidisciplinario de Posgrado en Ciencias Ambientales at the Universidad Autónoma de San Luis Potosí. This is with the intention of institutionalizing initiatives in Latin America and the Caribbean that experiment with this training path, and that environmental historians benefit from other organizational strategies presented.